2015
DOI: 10.1161/circep.115.002894
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of the Negative Component of the Unipolar Atrial Electrogram as an In Vivo Marker of Transmural Lesion Creation

Abstract: E lectrophysiological pulmonary vein isolation (PVI) is the cornerstone of paroxysmal atrial fibrillation (AF) ablation.1 However, the incidence of AF recurrence remains high and mostly because of PV reconnection, 2,3 emphasizing the need for more understanding of PVI durability and associated factors.In this regard, it has been elegantly shown in a swine model that elimination of the negative component of the unipolar atrial electrogram during radiofrequency applications reflects transmural lesions creation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…Furthermore, in view of the second-annotated site "per protocol" RF duration of ~9s, yet with near instantaneous pure R UE morphology change evident, most second-site RF applications were to at least that duration employed by Bortone et al when achieving single-site 100% histologically-confirmed TM lesions of 4.3mm depth. 16 Although it is scientifically invalid to draw firm conclusions from such comparisons (particularly when VISITAG™ Module annotation was not employed during these animal studies), together with the previously reported high procedural efficacy of this present CF and VISITAG™ Module-guided protocol 15 , it is very unlikely that RF application at these LAPW sites resulted in non-TM lesions. 15 All UE morphology data were collected retrospectively, so this report does not prove that modification of RF delivery based on real-time UE morphological assessment during VISITAG™ Module and CF-guided PVI is appropriate.…”
Section: Study Limitationsmentioning
confidence: 85%
See 2 more Smart Citations
“…Furthermore, in view of the second-annotated site "per protocol" RF duration of ~9s, yet with near instantaneous pure R UE morphology change evident, most second-site RF applications were to at least that duration employed by Bortone et al when achieving single-site 100% histologically-confirmed TM lesions of 4.3mm depth. 16 Although it is scientifically invalid to draw firm conclusions from such comparisons (particularly when VISITAG™ Module annotation was not employed during these animal studies), together with the previously reported high procedural efficacy of this present CF and VISITAG™ Module-guided protocol 15 , it is very unlikely that RF application at these LAPW sites resulted in non-TM lesions. 15 All UE morphology data were collected retrospectively, so this report does not prove that modification of RF delivery based on real-time UE morphological assessment during VISITAG™ Module and CF-guided PVI is appropriate.…”
Section: Study Limitationsmentioning
confidence: 85%
“…Furthermore, while increasing the RF duration to pure R + 5s resulted in histologically TM ablation in 100% without extra-cardiac thermal trauma, lesions terminated at pure R + 10s, +20s and "conventional" 30s total RF, although resulting in 100% pure R UE morphology and histologically proven TM ablation, had 11-17% occurrence of extra-cardiac thermal trauma. 16 Subsequently, the release of CARTOREPLAY™ (Biosense Webster) permitted assessment of UE morphology change following PVI employing this previously derived CF and VISITAG™-guided PVI protocol. These investigations demonstrated significantly shorter time to pure R UE morphology change at left-sided first-annotated LAPW sites (4.9s v 6.7s; p=0.02), associated with significantly greater impedance drop, compared to right-sided sites.…”
Section: Previous Investigations Demonstrated That Visitag™ Module (Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-five patients underwent first-time PVI as described, between November 2016 and May 2017: 13 persistent AF, 12 PAF; 19 male (76%); mean age 57 [SD: 14] years and mean CHA 2 DS 2 -VASc score 1.3 [SD: 1.3]. Complete PVI was achieved in all without spontaneous 11 / dormant recovery of PV conduction, following mean 16.2 [SD: 3.1] minutes of RF, with no procedural complications. The ACCURESP™-triggering cohort comprised 8 of 25 cases (32%); considering age, body mass index and RF duration required for case completion, there were no significant differences between the cohorts with and without ACCURESP™ threshold triggering.…”
Section: Resultsmentioning
confidence: 99%
“…(2) There was no incorporation of measures of the TM tissue response to RF delivery, yet in vivo animal studies have demonstrated that a change in the unipolar electrogram (UE) morphology from RS to "pure R" may be indicative of histologically-confirmed TM lesions. 10,11 Furthermore, a study conducted in humans has confirmed the utility of RF titration according to real-time assessments of pure R UE morphology change towards a highly effective CF-guided PVI protocol 12 ;…”
Section: Introductionmentioning
confidence: 90%